PENGARUH ECONOMIC VALUE ADDED DAN MARKET VALUE ADDED TERHADAP RETURN SAHAM - Delia, Delia; Sidik, Solihin (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2022)
The issues in this research is to find out, analyze and study the effect of partially and simultaneously Economic Value Added and Market Value Added on Stock Return of the pharmaceutical subsector companies listed on the Indonesia Stock Exchange for the period of 2015 -2019. The number of samples taken is 8 (eight) pharmaceutical subsector companies listed on the Indonesia Stock Exchange and have published complete annual financial reports during the study period.  The sampling technique used was purposive sampling. This research is expected to contribute to the development of the field of accounting, especially financial accounting. The research method used is a quantitative method with descriptive analysis of verification, based on the result of data analysis. The research obtained several conclusions as follow: EVA partially has a significant negative effect on stock return of pharmaceutical companies listed on the Indonesia Stock Exchange during the study period. Meanwhile, MVA partially has a significant positive effect on stock return of pharmaceutical companies listed on the Indonesia Stock Exchange during the study period. EVA and MVA have a positive and significant effcet simultaneously on the stock return of pharmaceutical companies listed on the Indonesia Stock Exchange during the study period.